Book Review of "My Street Money: A Street-Level View of Managing Your Money from the Heart to the Bank" - Jeffrey S Nelson (Journal of Financial Therapy, 2011)
In his book, My Street Money: A Street-Level View of Managing Your Money from the Heart to the Bank, Louis Barajas delivers a set of sound principles and actionable steps for an audience who consider themselves average citizens with traditional values.
Keywords: Financial Therapy